Ethanol Extraction from Fresh Algae (Gracilaria sp) Using Various Concentrations of Hydrochloric Acid Solution in The Hydrolysis Process - Putri E. Malinti; Grevo S. Gerung; Natalia D.C. Rumampuk; Markus T. Lasut; Nickson J. Kawung; Esther D. Angkouw (JURNAL PESISIR DAN LAUT TROPIS, 2025)
Bioethanol is ethanol obtained through the fermentation of biomass rich in starch or cellulose from plant materials. Gracilaria sp. algae is one potential biomass source because it contains 54.4% galactan and 19.7% cellulose. This content makes it a promising alternative raw material for bioethanol production. Until now, there has been no scientific report related to ethanol extraction from Gracilaria sp. originating from the waters of Gunung Kidul, Yogyakarta. This study aims to: (1) determine the presence of ethanol in Gracilaria sp.; (2) measure the volume of ethanol from distillation; and (3) test ethanol qualitatively using potassium dichromate and sulfuric acid reagents. The research procedures include sample preparation, hydrolysis with HCl of various concentrations (0.5–2 M), fermentation using Fermipan yeast, urea, EM4, and NaOH (pH 4), and fermentation for 5 days. Distillation was carried out at a temperature of 78–80°C and the results were tested qualitatively by a color change from orange to blue as an indicator of ethanol. The results showed that Gracilaria sp. can produce ethanol, and the qualitative test method used has proven effective, simple, and economical. Further research is recommended to improve the purity and efficiency of bioethanol production from Gracilaria sp. Keywords: algae, bioethanol, Gracilaria sp., ethanol, qualitative ethanol analysis.   Abstrak Bioetanol adalah etanol yang diperoleh melalui fermentasi biomassa yang kaya akan pati atau selulosa dari bahan nabati. Alga Gracilaria sp. merupakan salah satu sumber biomassa potensial karena mengandung 54,4% galaktan dan 19,7% selulosa. Kandungan ini menjadikannya bahan baku alternatif yang menjanjikan untuk produksi bioetanol. Hingga kini, belum ada laporan ilmiah terkait ekstraksi etanol dari Gracilaria sp. yang berasal dari perairan Gunung Kidul, Yogyakarta. Penelitian ini bertujuan untuk mengetahui keberadaan etanol dalam Gracilaria sp. mengukur volume etanol hasil distilasi,dan menguji etanol secara kualitatif menggunakan pereaksi kalium dikromat dan asam sulfat. Prosedur penelitian meliputi persiapan sampel, hidrolisis dengan HCl berbagai konsentrasi (0,5–2 M), fermentasi menggunakan ragi Fermipan, urea, EM4, dan NaOH (pH 4), serta fermentasi selama 5 hari. Distilasi dilakukan pada suhu 78–80°C dan hasilnya diuji kualitatif dengan perubahan warna dari oranye ke biru sebagai indikator etanol. Hasil menunjukkan bahwa Gracilaria sp. dapat menghasilkan etanol dan metode uji kualitatif yang digunakan terbukti efektif, sederhana, dan ekonomis. Penelitian lanjutan disarankan untuk meningkatkan kemurnian dan efisiensi produksi bioetanol dari Gracilaria sp Kata kunci: alga, bioetanol, Gracilaria sp, Etanol, analisis kualitatif etanol